Proceedings - 12th International Equitation Science Conference - Understanding horses to improve training and performance. June 23-25, 2016 • French National Riding School • Saumur • France (French National Riding School, 2016)
The entire conference (academic part and practical day) was hosted by the French Institute for Horse and Riding (Ifce) within the French National Riding School. The Ifce is the French public operator which aims at promoting the professionalization of the French horse industry. The French National Riding School of Saumur is home to the well-known 'Cadre Noir de Saumur' and is the custodian of the French tradition of horse riding, recognised as intangible heritage by UNESCO.